Characterization of American Football Injuries in Children and Adolescents. Issue 2 (February 2018) - Smith, Patrick J.; Hollins, Anthony M.; Sawyer, Jeffrey R.; Spence, David D.; Outlaw, Shane; Kelly, Derek M.
Abstract : Background: As a collision sport, football carries a significant risk of injury, as indicated by the large number of pediatric football-related injuries seen in emergency departments. There is little information in the medical literature focusing on the age-related injury patterns of this sport. Our purpose was to evaluate the types of football-related injuries that occur in children and adolescents and assess which patient characteristics, if any, affect injury pattern. Methods: Retrospective chart review was performed of football-related injuries treated at a level 1 pediatric referral hospital emergency department and surrounding urgent care clinics between January 2010 and January 2014. Patients with e-codes for tackle football selected from the electronic medical record were divided into 4 age groups: younger than 8 years old, 8 to 11, 12 to 14, and 15 to 18 years. Data collected included diagnosis codes, procedure codes, and hospital admission status. Results: Review identified 1494 patients with 1664 football-related injuries, including 596 appendicular skeleton fractures, 310 sprains, 335 contusions, 170 closed head injuries, 62 dislocations, 9 spinal cord injuries, and 14 solid organ injuries. There were 646 (43.2%) athletes with upper extremity injuries and 487 (32.6%) with injuries to the lower extremity. Hospital admissions were required in 109 (7.3%) patients. Fracture was the most common injury in all four patient age groups, but occurred at a lower rate in the 15 to 18 years old age group. The rate of soft tissue injury was higher in the 15 to 18 years old age group. The rate of closed head injury, which included concussions, was highest in the younger than 8 years old age group. Conclusions: Age does influence the rates of certain football-related injuries in children and adolescents. Fractures decrease with increasing age, while the rate of soft tissue trauma increases with increasing age. Younger patients (younger than 8 y old) trended toward higher rates of closed head injury compared with other age groups. Awareness of these variations in injury patterns based on age could result in age-specific changes in equipment, training, and safety rules. Level of Evidence: Level IV—case series.